High resolution digital sensing and mapping method for quantifying soil surface roughness after tillage operations - Yahya, Azmi; Wee, Beng Sui (2008)
An automated, trailed type 2-axis laser soil surface profile digitizer has been developed to be used with a Massey Ferguson 3060 to quantify the soil surface profile after a tillage operation. The first field test was conducted to evaluate the effect of tillage operation on the average elevation height, Degree of tilth and Random Roughness Index of the resulted soil surface. The tested tillage operations include disk plowing, moldboard plowing, disk harrowing after disk plowing, disk harrowing after moldboard plowing, rotary tilling after disk plowing, and rotary tilling after moldboard plowing. The second test was conducted to evaluate the effects of tractor travel speed and rotary tiller speed on the random Roughness Index of the produced soil surface profile. Generally, the Roughness index measured by the digitizer seems to be the best indicator over average elevation height and degree of tilth for quantifying soil surface profile after tillage operations.